2021
DOI: 10.3389/fphar.2021.705402
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis sativa L. (var. indica) Exhibits Hepatoprotective Effects by Modulating Hepatic Lipid Profile and Mitigating Gluconeogenesis and Cholinergic Dysfunction in Oxidative Hepatic Injury

Abstract: Cannabis sativa L. is a crop utilized globally for recreational, therapeutic, and religious purposes. Although considered as an illicit drug in most countries, C. sativa until recently started gaining attention for its medicinal application. This study sought to investigate the hepatoprotective effect of C. sativa on iron-mediated oxidative hepatic injury. Hepatic injury was induced ex vivo by incubating hepatic tissues with Fe2+, which led to depleted levels of reduced glutathione, superoxide dismutase, catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 73 publications
2
15
0
1
Order By: Relevance
“…Interestingly, Usami and colleagues, in an ex vivo experiment using mouse hepatic microsomes, found that CBD and its hydroxy-quinone derivatives produced by CYP3A11 reduced the activity of SOD and catalase [ 38 ]. On the contrary, in another ex vivo model in which FeSO 4 was employed to induce oxidative stress in isolated hepatic tissue, leading to decreased activity of SOD and catalase, CBD treatment enhanced the antioxidant defense, including SOD and catalase activity [ 39 ]. The authors suggested that this contributes to the hepatoprotective effect of CDB and Cannabis sativa .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Usami and colleagues, in an ex vivo experiment using mouse hepatic microsomes, found that CBD and its hydroxy-quinone derivatives produced by CYP3A11 reduced the activity of SOD and catalase [ 38 ]. On the contrary, in another ex vivo model in which FeSO 4 was employed to induce oxidative stress in isolated hepatic tissue, leading to decreased activity of SOD and catalase, CBD treatment enhanced the antioxidant defense, including SOD and catalase activity [ 39 ]. The authors suggested that this contributes to the hepatoprotective effect of CDB and Cannabis sativa .…”
Section: Discussionmentioning
confidence: 99%
“…Glucose toxicity characterised by hepatic glucose accumulation promotes hepatic oxidative stress which results in severe liver oxidative injury and eventual hepatic cell death ( Chandrasekaran et al, 2012 ; Mota et al, 2016 ). Reports have shown the protective property of various plant-based antioxidants in scavenging free radical and the improvement of liver carbohydrate metabolism ( Yazdi et al, 2019 ; Erukainure et al, 2021a ; Olofinsan et al, 2022 ). This is in accordance with the ability of L. javanica herbal infusion to significantly reduce the activities of glucose-6-phosphatase, fructose-1,6-bisphosphatase and glycogen phosphorylase in oxidative hepatic injury ( Figures 6A–C ), suggesting a hepatoprotective and hepatic metabolic function-improving potential of the herbal tea infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Excess cellular levels of glucose and lipids can serve as substrates for the generation of glucotoxic and lipotoxic species, respectively, which can cause damage to biomolecules, induce metabolic stress and eventual cell death ( Mota et al, 2016 ; Chen et al, 2020 ). Additionally, altered cholinergic enzyme activities have been implicated in the pathogenesis of liver diseases and studies have reported oxidative stress as facilitator of cholinergic dysfunction ( Garcia-Ayllon et al, 2012 ; Erukainure et al, 2021a ). These corroborates the use of antioxidants as therapies for targeting oxidative stress in the management of liver diseases ( Upadhyay et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, both CBD and THC are metabolised by CYP2C9, suggesting the possibility of impaired drug clearance [ 109 ] or renal/liver toxicity. However, there are no data to suggest CBD and THC cause renal/liver toxicity, and in fact there is data to suggest hepatoprotective effects [ 110 ] and prevention of cisplatin-induced renal toxicity [ 111 ]. However safety profiles of MC in the context of cancer care remains superficially addressed, underscoring the importance of regular renal and liver function tests, appropriately titrated dosing, and studies with co-primary endpoints that address efficacy and safety [ 88 ].…”
Section: Using Medicinal Cannabis During Active Cancer Treatment: Pre...mentioning
confidence: 99%